THE ROLE OF COLLABORATIVE GOVERNANCE IN DISASTER RESPONSE: INSIGHTS FROM TRANSNATIONAL EMERGENCY MANAGEMENT - Ni Putu Ari Setiawati; Ni Made Hintya Mahayani (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study explores the role of collaborative governance in enhancing disaster response effectiveness, particularly within the context of transnational emergency management. As disasters increasingly transcend borders due to globalization and climate change, conventional state-centric approaches often fall short in addressing complex, multi-jurisdictional crises. Drawing upon a comprehensive literature review, this research synthesizes key theoretical perspectives and empirical findings on collaborative governance mechanisms, including public-private partnerships, intergovernmental coordination, and cross-sectoral stakeholder engagement. The study highlights how trust-building, joint decision-making, and institutional flexibility contribute to improved coordination, resource sharing, and resilience in transboundary disaster contexts. Moreover, it identifies challenges such as power asymmetries, institutional fragmentation, and cultural differences that may hinder collaboration. The findings offer insights for policymakers and emergency managers seeking to build more adaptive and inclusive disaster governance frameworks. The study concludes that collaborative governance is not merely a normative ideal but a practical necessity in managing transnational disasters effectively.